Contemporary Review on Craniectomy and Cranioplasty; Part 1: Decompressive Craniectomy. Issue 3 (27th May 2022) - Hatamleh, Muhanad M.
Abstract : Abstract: This paper aims to review clinical benefits of decompressive craniectomy (DC) in both adult and paediatric populations; its indications and factors contributing to its postoperative success. The Glasgow Outcome Scale and the Modified Rankin Scale are the most commonly used scales to assess the long-term outcome in patients post DC. In adult traumatic brain injury patients, 2 randomized clinical trials were carried out; DECRA (Decompressive Craniectomy in Diffuse Traumatic Brain Injury) and RESCUEicp (Randomised Evaluation of Surgery with Craniectomy for Uncontrollable Elevation of inter cranial pressure) employing collectively 555 patients. Despite the differences in these trials, their initial results affirm DC can lead to reduced mortality and more favorable outcomes. In ischemic stroke adult patients, different clinical trials of HAMLET (Dutch trial of Hemicraniectomy after middle cerebral artery infarction with life-threatening Edema), DESTINY (German trial of Decompressive Surgery for the treatment of Malignant Infarct of the Middle Cerebral Artery), and DECIMAL (French trial of Decompressive Craniectomy in Malignant Middle Cerebral Artery Infarcts) suggested that DC improves survival compared with best medical management, but with an increased proportion of treated individuals surviving with moderate or severe disability. With regard to the size of bone to be removed, the larger the defect the better the results with a minimum diameter of 11 to 12 cm of bone flap. Cranioplasty timing varies and ranges from 6 weeks to more than 12 months post DC, depending on completion of medical treatment, clinical recovery, resolution of any infection, and an evaluation of soft tissues at the defect site.